2001
DOI: 10.1007/s004280100489
|View full text |Cite
|
Sign up to set email alerts
|

Keratoameloblastoma with unique histological architecture: an undescribed variation of ameloblastoma

Abstract: Keratoameloblastoma is an extremely rare variant of ameloblastoma, and a review of the English language literature yields only several documented cases of ketatoameloblastoma. This paper reports a keratoameloblastoma showing unique histological architecture. The patient was a 76-year-old Japanese man with a multilocular radiolucent lesion of the mandible extending from the left canine to the second molar area. Microscopically, the lesion was characterized by multicystic spaces lined by papillary projections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…4,13 The other possibility, demonstrated in the present case, is that the radiopacity is best described as extensive keratinization based on microscopic examination. Whether the radiopacity reflects extensive keratin or hard tissue material developed from accumulated keratin, it is a distinctive radiological feature of keratoameloblastoma.…”
Section: Accepted Manuscriptmentioning
confidence: 84%
See 2 more Smart Citations
“…4,13 The other possibility, demonstrated in the present case, is that the radiopacity is best described as extensive keratinization based on microscopic examination. Whether the radiopacity reflects extensive keratin or hard tissue material developed from accumulated keratin, it is a distinctive radiological feature of keratoameloblastoma.…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…Reviews and reports in the extant English-language literature discuss only 11 cases. [4][5][6][7][8][9][10][11][12] Prior reports have focused on the histological features of keratoameloblastoma, while little attention has so far been paid to its radiological features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the previous studies have not reported a different biologic behavior, growth rate and pattern, and histologic changes to malignancy (such as cellular atypia) of keratoameloblastoma from other subtypes of ameloblastoma, it can be treated by the same protocol as ameloblastoma, including resection with a suitable bone margin (1Y2 cm). 3,4,7,11,12,19 The variation in the histopathology of ameloblastoma sometimes gives rise to individual cases that do not fit the commonly used classification systems and therefore are confusing to the pathologists and clinicians who must identify and treat them. Keratoameloblastoma is also one of these variants, albeit very rare but can compromise the correct diagnosis and treatment of a benign but aggressive and destructive lesion (ameloblastoma).…”
Section: Discussionmentioning
confidence: 98%
“…13 Thus, a well-vascularized free flap is suitable for reconstructing the defect after surgical resection of an AVM. 13,19 We used a latissimus dorsi free flap to provide bulk and stability in the defect, in addition to restoring hemodynamics. 20 Alternatively, the anterolateral thigh and deep inferior epigastric artery perforator flaps can be used to treat large defects in the head and neck.…”
mentioning
confidence: 99%